Legal Problems regarding the Crime of Fake News (Hoax) during the Covid-19 Pandemic - Sitepu, Yosua Prima Arihta; Mulyadi, Mahmud; Ekaputra, M.; Marlina, Marlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
The problem of spreading fake news/hoaxes. This happens almost all over the world, including Indonesia. One example of hoaxes in Indonesia is the spread of false information in North Sumatra province, especially through social media. Thesis writing technique This research approach is a normative legal system. The results of the study show that Developing a Criminal Law Policy to Combat False Information Crimes Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning the Criminal Code, Law no. 1 of 1946 concerning Criminal Law Regulations, and Law Number 1 of 2023 concerning Electronic Transaction Information (ITE). Provisions related to the COVID-19 pandemic are in the updated Criminal Code.